THE EFFECTIVENESS OF THE TOKOPEDIA CASHBACK PROGRAM ON INCREASING GENERATION Z CONSUMERS' BUYING INTEREST - Amelia Amelia; Jumriah Basri (Jurnal Mahasiswa Manajemen, 2025)
Cashback programs have become one of the most popular digital marketing strategies used by various e-commerce platforms to encourage consumer purchasing decisions. This study was conducted to examine the effectiveness of Tokopedia’s cashback program in increasing purchase intention, particularly among Generation Z, who are known for their high levels of consumption and sensitivity to price offers and promotions. The research employed a quantitative approach, distributing questionnaires to respondents aged 18 to 27 who actively make transactions on Tokopedia. The collected data were then analyzed through validity, reliability, and simple linear regression tests to measure the relationship between the cashback program and consumer purchase intention. This study is expected to provide an empirical overview of the effectiveness of cashback programs on Generation Z shopping behavior and offer recommendations for e-commerce actors to develop more relevant, appealing, and sustainable promotional strategies.